Diagnosing Homo sapiens in the fossil record. (July 2014) - Stringer, Christopher Brian; Buck, Laura Tabitha
Abstract Background: Diagnosing Homo sapiens is a critical question in the study of human evolution. Although what constitutes living members of our own species is straightforward, in the fossil record this is still a matter of much debate. The issue is complicated by questions of species diagnoses and ideas about the mode by which a new species is born, by the arguments surrounding the behavioural and cognitive separateness of the species, by the increasing appreciation of variation in the early African H. sapiens record and by new DNA evidence of hybridization with extinct species. Methods and results: This study synthesizes thinking on the fossils, archaeology and underlying evolutionary models of the last several decades with recent DNA results from both H. sapiens and fossil species. Conclusion: It is concluded that, although it may not be possible or even desirable to cleanly partition out a homogenous morphological description of recent H. sapiens in the fossil record, there are key, distinguishing morphological traits in the cranium, dentition and pelvis that can be usefully employed to diagnose the H. sapienslineage. Increasing advances in retrieving and understanding relevant genetic data provide a complementary and perhaps potentially even more fruitful means of characterizing the differences between H. sapiens and its close relatives.